2019
DOI: 10.15835/nbha47411617
|View full text |Cite
|
Sign up to set email alerts
|

Total Phenol, Antioxidant and Allelopathy Assay, and Meiosis Study of Lampranthus spectabilis and Aptenia cordifolia

Abstract: Lamperanthus spectabilis and Aptenia cordifolia (Aiozaceae) are two ornamental plants. A little information is available about their active compounds and meiosis’ process.  In this study, the phenolic content, antioxidant activity, allelopathy effects and meiosis’ process of pollen mother cells of L. spectabilis and A. cordifolia were studied. The alcohol extract was used for phenol, antioxidant and allelopathy assay along with young buds for meiosis study. The stamens and petals of both plants possessed the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The species Lampranthus francisci showed strong anticandidal activity . Moreover, studies showed that Lampranthus spectabilis has high phenolic content and displays strong antioxidant activity . Lampranthus coccineus SNPs showed remarkable antioxidant and anti‐Alzheimer's activity .…”
Section: Introductionmentioning
confidence: 99%
“…The species Lampranthus francisci showed strong anticandidal activity . Moreover, studies showed that Lampranthus spectabilis has high phenolic content and displays strong antioxidant activity . Lampranthus coccineus SNPs showed remarkable antioxidant and anti‐Alzheimer's activity .…”
Section: Introductionmentioning
confidence: 99%